Museum Guide Application Menggunakan Augmented Reality Berbasis Android: (Studi Kasus : Museum Ketransmigrasian Lampung) - Agustinus Eko Setiawan; Dinda Rahmadanty; Ratnasari; Dwi Yana Ayu Andini (LogicLink, 2024)
This research develops a museum guide application using Android-based Augmented Reality (AR) technology, with a focus on the Lampung Transmigration Museum. The purpose of this research is to improve visitors' educational experience and attract more tourists by presenting museum collection information interactively and visually. The research methods used are qualitative and quantitative approaches, as well as the Multimedia Development Life Cycle (MDLC) model consisting of concept, design, material collection, assembly, testing, and distribution stages. The results showed that this application succeeded in increasing visitor attraction and engagement, as well as providing easier access to information about museum collections. Tests show that the marker can be detected well within a distance of 8 to 50 cm, and can still be recognized even if it is obstructed by 50%. It is hoped that this application can be a practical solution in delivering information in museums, as well as increasing public interest in cultural heritage